Capitalist firm vis-a-vis trade union, versus producer cooperative - Istvan R. Gabor (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2004)
By way of presenting an ahistorical fictitious story, this paper is ment to illustrate that: - in contrast to conventional wisdom, trade unions, in their symbiosis with capitalist firms, may further rather than impede price-mediated self-regulation in the labour market via their involvement in wagesetting, - whereas producer co-operatives, although they might seem to represent a close collateral of fully unionized capitalist firms, are fundamentally at variance with the logic of market self-regulation, in that they tend to respond to an increase in demand by restraining rather than extending supply, - with the consequence that they cannot even in principle be an alternative to capitalist firms, at least on a mass scale, unless combined with the adoption of some kind of bureaucratic price control.
Keywords: 330